FATIGUE ANALYSIS OF AN ALUMINUM AIRPLANE SPAR STRUCTURE - Nonato, Raphael Basilio Pires; Fonseca, Thiago Escossia da (Revista Ciências Exatas, 2017)
Airplane is the intercontinentally most widely used mean of passenger transportation. It has a great importance on the actual global economy not only due to passenger and cargo transportation around the world, but also for its remarkable impact on industrial activity, commerce and services. Therefore, the accurate design of airplane components is of prime relevance in the context of the security of its complex operations. Following this reasoning, the spar, which is the principal element of the wing, plays a crucial role in airplane assembly because it supports the greatest part of the external loads. Although some research related to spar structures have been undertaken aiming to find maximum stresses and fatigue life, more studies have to be conducted, showing that the fatigue life prediction of this component still deserve attention. This paper aims to obtain the fatigue life of a non-tapered cantilevered aluminum spar of a single-engine airplane subjected to several point loads (coming from the interface with adjacent wing components) acting on the center of gravity of the distributed loads resultant from these contacts. The mathematical model comprises an I-beam, which one end is cantilevered at wing box (fuselage) and the other is free and almost reaches the airplane wing tip. The spar model is generated using ANSYS® Design Modeler and is computationally assessed using the Finite Element Method (FEM)-based software ANSYS® Mechanical. The results of this analysis show that it is possible to predict fatigue life of a spar under the considerations presented herein. Therefore, the life obtained as a result of this analysis can be used to plan the maintenance of this component, leading to more reliable inspection intervals, which could avoid catastrophic failures under service and operate with a better cost-benefit relation.